Dampak Sosial Ekonomi BLT terhadap Masyarakat Miskin di Kabupaten Tulungagung - Ismail, H. M. (Universitas Brawijaya, Indonesia, 2009)
The arising of the world crude oil's price has worsen the economic condition of Indonesia. The increasing charge of APBN because of subsidy's, increasing, has forced the government to raise the price of domestic BBM. This policy cause the number of the poor of increases. So, the government conduct the program of BLT that is dedicated to the poor families in order to maintain the purchasing ability or to arise their prosperity but in the practice, the program of BLT is full of problem and influencing the poor. This research is conducted to understand the mechanism in distributing BLT in sub province of Tulungagung, and abserve is social an economic effect to word poor people in tulungagung . this research is descriptive research by using cualitative approach, by using the method of taking note of the fact that is abserve in collecting data using the method of observation, interview, and also conducting documentation. Generally BLT create positive social and economic effect to the society, the fund(BLT) function as the capital business activity, as their health fund, etc. however, for some cases, it causes conflict and disharmonious relationship in the society. It can also causes other psychological problem (such as laziness, frustration, etc).